2001
DOI: 10.1086/323496
|View full text |Cite
|
Sign up to set email alerts
|

Multiwavelength Observations of the Soft Gamma Repeater SGR 1900+14 during Its 2001 April Activation

Abstract: The soft-gamma repeater SGR 1900+14 became active on 18 April 2001 after about two years of quiescence; it had remained at a very low state of activity since the fall of 1998, when it exhibited extraordinary flaring. We have observed the source in the gamma and X rays with Ulysses and Chandra , and in the radio with MERLIN. We report here the confirmation of a two component X-ray spectrum (power law + blackbody), indicating emission from the neutron star surface. We have determined that there is a dust halo su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
58
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 16 publications
7
58
1
Order By: Relevance
“…We measure 2-10 keV rms pulse fractions of 18.1(10)%, 16.3(11)%, 13.6(15)%, and 12.9(12)% for the respective epochs of MJD TDB 52,018.113 (SAX), 52,021.324 (CXO), 52,029.591 (SAX), and 52,030.092 (CXO). Note that the measured CXO pulse fractions differ slightly from those reported in Kouveliotou et al (2001), who reported the pulse fractions in the 0.5-7.0 keV energy range. The pulse fraction of SGR 1900+14 increases significantly following the April 18 flare, and during the subsequent 11 days slowly declines, approaching its quiescent value.…”
Section: Pulse Profile and Fractioncontrasting
confidence: 90%
“…We measure 2-10 keV rms pulse fractions of 18.1(10)%, 16.3(11)%, 13.6(15)%, and 12.9(12)% for the respective epochs of MJD TDB 52,018.113 (SAX), 52,021.324 (CXO), 52,029.591 (SAX), and 52,030.092 (CXO). Note that the measured CXO pulse fractions differ slightly from those reported in Kouveliotou et al (2001), who reported the pulse fractions in the 0.5-7.0 keV energy range. The pulse fraction of SGR 1900+14 increases significantly following the April 18 flare, and during the subsequent 11 days slowly declines, approaching its quiescent value.…”
Section: Pulse Profile and Fractioncontrasting
confidence: 90%
“…In quiescence, the X-ray spectrum of SGR 1900+14 is best fitted (Woods et al 1999) by the sum of a BB (kT ' 0:5 keV) and a power law ( photon index À ' 1:0-2.5). For this model, the column density is consistently measured at N H ' 2:5 ; 10 22 cm À2 (Woods et al 1999(Woods et al , 2001Kouveliotou et al 2001;Feroci et al 2003). However, the particular observation in which our bursts were recorded took place during a state of enhanced flux following the 2001 April 18 flare (Feroci et al 2003), in a so-called afterglow state.…”
Section: Bepposax Mecs and Pds Spectral Analysismentioning
confidence: 71%
“…The strongest of these "intermediate" flares was observed on April 18, 2001 from SGR 1900+14 [108,74]. It lasted about 40 s and showed pulsations at the NS rotation period, as in the tails of giant flares, but it lacked an initial spike.…”
Section: Bursts and Flaresmentioning
confidence: 99%